Differences in tumor-to-normal organ SUV ratios measured with 68Ga-DOTATATE PET compared with 177Lu-DOTATATE SPECT in patients with neuroendocrine tumors. Issue 8 (10th June 2022) - Wong, Ka Kit; Frey, Kirk A.; Niedbala, Jeremy; Kaza, Ravi K.; Worden, Francis P.; Fitzpatrick, Kellen J.; Dewaraja, Yuni K.
Abstract : Background: Our goal is to quantitatively compare radiotracer biodistributions within tumors and major normal organs on pretherapy 68 Ga-DOTATATE PET to post-therapy 177 Lu-DOTATATE single-photon emission computed tomography (SPECT) in patients receiving peptide receptor radionuclide therapy (PRRT). Methods: PET/CT at 60 min postinjection of Ga-68 DOTATATE and research 177 Lu-SPECT/CT imaging at 4 h (SPECT1) and 24 h (SPECT2) post-cycle#1 were available. Manual contours of lesions on baseline CT or MRI were applied to co-registered SPECT/CT and PET/CT followed by deep learning-based CT auto-segmentation of organs. Tumor-to-normal organ ratios (TNR) were calculated from standardized uptake values (SUV)mean and SUVpeak for tumor, and SUVmean for non-tumoral liver (nliver), spleen and kidney. Results: There were 90 lesons in 24 patients with progressive metastatic neuroendocrine tumor. The correlation between PET and SPECT SUV TNRs were poor/moderate: PET versus SPECT1 R 2 = 0.19, 0.21, 0.29; PET versus SPECT2 R 2 = 0.06, 0.16, 0.33 for TNRnliver, TNRspleen, TNRkidney, respectively. Across all patients, the average value of the TNR measured on PET was significantly lower than on SPECT at both time points ( P < 0.001). Using SUVmean for tumor, average TNR values and 95% confidence intervals (CI) were PET: TNRnliver = 3.5 [CI: 3.0-3.9], TNRspleen = 1.3 [CI, 1.2-1.5], TNRkidney = 1.7 [CI: 1.6-1.9]; SPECT1: TNRnliver = 10 [CI: 8.2-11.7], TNRspleen = 2.9 [CI: 2.5-3.4], TNRkidney = 2.8 [CI: 2.3-3.3]; SPECT2: TNRnliver = 16.9 [CI: 14-19.9], TNRspleen = 3.6 [CI: 3-4.2], TNRkidney = 3.6 [CI: 3.0-4.2]. Comparison of PET and SPECT results in a sphere phantom study demonstrated that these differences are not attributed to imaging modality. Conclusions: Differences in TNR exist for the theranostic pair, with significantly higher SUV TNR on 177 Lu SPECT compared with 68 Ga PET. We postulate this phenomenon is due to temporal differences in DOTATATE uptake and internalization in tumor as compared to normal organs.